2015
DOI: 10.1088/1009-0630/17/3/02
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Emission Behavior in the Soft X-Ray and Extreme Ultraviolet Range on EAST

Abstract: A Michelson interferometer, on loan from EFDA-JET (Culham, United Kingdom) has recently been commissioned on the experimental advanced superconducting tokamak (EAST, ASIPP, Hefei, China). Following a successful in-situ absolute calibration the instrument is able to measure the electron cyclotron emission (ECE) spectrum, from 80 GHz to 350 GHz in extraordinary mode (X-mode) polarization, with high accuracy. This allows the independent determination of the electron temperature profile from observation of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was surmised that other impurity lines might overlap with them, which would have an effect on the fitting results of ion and electron temperature. The W XLIV at 3.963 60 Å and W XLV at 3.973 00 Å diffracted by He-like crystal of the first order were identified on the side of the X and Y lines, respectively, since the upper divertors on EAST contain a large amount of tungsten [13], and the existence of these tungsten lines were most likely due to the ionization of tungsten at high electron temperatures, especially during the H-mode phase. It is also noted that the W XLVIII at 3.691 00 Å marked in red indicated that this line was diffracted by H-like crystal though it was located in He-like argon spectra.…”
Section: Analysis Of Impurity Linesmentioning
confidence: 98%
“…It was surmised that other impurity lines might overlap with them, which would have an effect on the fitting results of ion and electron temperature. The W XLIV at 3.963 60 Å and W XLV at 3.973 00 Å diffracted by He-like crystal of the first order were identified on the side of the X and Y lines, respectively, since the upper divertors on EAST contain a large amount of tungsten [13], and the existence of these tungsten lines were most likely due to the ionization of tungsten at high electron temperatures, especially during the H-mode phase. It is also noted that the W XLVIII at 3.691 00 Å marked in red indicated that this line was diffracted by H-like crystal though it was located in He-like argon spectra.…”
Section: Analysis Of Impurity Linesmentioning
confidence: 98%
“…In the MHD-free phase at 4.18 s (t1 in figure 6(a)), there are no MHD mode and no magnetic reconnection. The hollow distribution of SXR profiles in figure 6(b) is a result of plasma impurities [22]. The impurities lead to strong radiation loss in the core and then cause the precursor MHD mode of = m 2.…”
Section: Locations Of Fast Electron and Its Generationmentioning
confidence: 97%
“…[2] Impurity accumulation is found to be more severe for heavier impurity species. [3] On the EAST tokamak, heavy impurity species are mainly from metal impurities such as iron, copper, molybdenum, and tungsten, [4] and impurity accumulation is often observed, especially during the high-density H-mode plasma operations.…”
Section: Introductionmentioning
confidence: 99%